Surface-grating deflection of fast atom beams - Zugarramurdi, A. (2013)
For energetic atomic beams grazingly incident at the surface along the low index directions, fast motion parallel to the surface and slow motion perpendicular to the surface lead to the quantum diffraction pattern in the scattered beam. In this experimental and theoretical joint study we show that when the incident beam is misaligned with respect to an axial channel, the characteristic deformation of the diffraction pattern reflects an overall deflection of the scattered beam from the specular direction. The deflection is maximum for the azimuthal misalignment angles close to the rainbow angle and we show how this effect can be explained with the detailed balance principle relating diffraction of misaligned and perfectly aligned beams. We also demonstrate that using the detailed balance principle the diffraction charts for the incident beams aligned along the axial channel can be reconstructed from the azimuthal incidence angle dependence of the data obtained with misaligned beams.